The FIGO Stage IVA Versus IVB of Ovarian Cancer: Prognostic Value and Predictive Value for Neoadjuvant Chemotherapy. Issue 3 (1st March 2018) - Tajik, Parvin; van de Vrie, Roelien; Zafarmand, Mohammad H.; Coens, Corneel; Buist, Marrije R.; Vergote, Ignace; Bossuyt, Patrick M.M.; Kenter, Gemma G.
Abstract : Objective: The revised version of the International Federation of Gynaecology and Obstetrics (FIGO) staging system (2014) for epithelial ovarian cancer includes a number of changes. One of these is the division of stage IV into 2 subgroups. Data on the prognostic and predictive significance of this classification are scarce. The effect of neoadjuvant chemotherapy (NACT) versus primary debulking surgery (PDS) in relation to the subclassification of FIGO stage IV is also unknown. Methods: We used data of the EORTC 55971 trial, in which 670 patients with previous stage IIIC or IV epithelial ovarian cancer were randomly assigned to PDS or NACT; 160 patients had previous stage IV. Information on previous FIGO staging and presence of pleural effusion with positive cytology were used to classify tumors as either stage IVA or IVB. We tested the association between stage IVA/IVB and survival to evaluate the prognostic value and interactions between stage, treatment, and survival to evaluate the predictive performance. Results: Among the 160 participants with previous stage IV disease, 103 (64%) were categorized as stage IVA and 57 (36%) as stage IVB tumors. Median overall survival was 24 months in FIGO stage IVA and 31 months in stage IVB patients ( P = 0.044). Stage IVB patients treated with NACT had 9 months longer median overall survival compared with IVB patients undergoing PDS ( P = 0.025), whereas in IVA patients, no significant difference was observed (24 vs 26 months, P = 0.48). Conclusions: The reclassification of FIGO stage IV into stage IVA or IVB was not prognostic as expected. Compared with stage IVA patients, stage IVB patients have a better overall survival and may benefit more from NACT.